Regional National Income Analysis (PAD) North Sulawesi Cooperation Area - Olilingo, Fahrudin Zain; Putri, Aulia Salsabillah; Santoso, Ivan Rahmat (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2023)
This research aims to find out the Regional Native Income Analysis (PAD) in the North Cooperation Area of Sulawesi. The data used is secondary data obtained from various other parties such as the Badan Pusat Statistik (BPS), Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah (DPPKAD), and other literature. The data used is taken based on a period of 10 years. The type of data used is panel data and the analysis used is multiple linear regression analysis. The results of this study showed that Regional Taxes had a positive and significant effect on PAD in Kawasan Kerjasama Utara Sulawesi, the Regional Levy had a negative and significant effect on PAD in Kawasan Kerjasama Utara Sulawesi, regional taxes and regional levies simultaneously had a positive and significant effect on PAD in Kawasan Kerjasama Utara Sulawesi.